PENGARUH KOMUNIKASI ANTAR PRIBADI TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN DAERAH PROVINSI SULAWESI TENGAH - Wulandari, Farisya (Katalogis, 2017)
This study aimed to examine the effect of independent variable interpersonal communication on employees performance. The data in this study were collected by the method of observation, questionnaires and documentations. Data analysis techniques used multiple regression analysis. The population in this study is all employees in Departement of Education and Cultural of Central Sulawesi Province as many as 182 people. The sampling technique used is proportional random sampling, which took samples of the number of respondents as many as 125 employees. The theory used the principle of interpersonal communication from Devito, while the performance used Mathis and Jackson theory. The results of this study partially showed the dominant dimension of interpersonal communication significantly affect to the performance of employees in Departement of Education and Cultural of Central Sulawesi Province is Postiveness (X1.4), while the lowest determination partial are Emphaty (X1.2) and Equality (X1.5) Simultaneously, a positive and significant relationship between communication interpersonal and employee performance by 0.322 or 32,2% with the level of the relationship amounted to 56,8% which means included in the category of Low influence. This case suggests that interpersonal communication is not the main aspect that affect the performance on the employees of departement of education and culture of Central Sulawesi Province, there are 67,8 %Â or 0,678 the effect of other variables not included in this study.